2011
DOI: 10.1139/l11-008
|View full text |Cite
|
Sign up to set email alerts
|

Deicing salt scaling resistance of concrete incorporating fly ash and (or) silica fume: laboratory and field sidewalk test data

Abstract: Sidewalk sections were cast in fall 2002 with three concrete mixtures that consisted of a control concrete, a concrete mixture incorporating 25% fly ash, and a concrete mixture made with a ternary blended cement (fly ash and silica fume). The curing practices consisted of using curing compound and wet burlap. For each of the sidewalk sections, laboratory specimens were cast on site using the concrete from the same batch. Large slabs (1.2 m × 0.9 m) were also cast from which specimens could be cored and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The problem becomes larger, when the fly ash dosage increases. Both [8] and [9] show that the salt frost scaling of concrete with high volumes of fly ash is reduced significantly, if the start of the freeze/thaw exposure is postponed to 91 or 180 days after casting.…”
Section: Introductionmentioning
confidence: 99%
“…The problem becomes larger, when the fly ash dosage increases. Both [8] and [9] show that the salt frost scaling of concrete with high volumes of fly ash is reduced significantly, if the start of the freeze/thaw exposure is postponed to 91 or 180 days after casting.…”
Section: Introductionmentioning
confidence: 99%
“…The curing regime consists of the same initial curing procedure as ASTM C672 and MTO LS-412 but requires on additional step before freeze thaw cycling can take place. This step requires the re-saturation of the surface using a 3% NaCl solution and is meant to partially simulate the field conditions of new concretes exposed to low concentration salt solutions during a first winter (Bouzoubaâ et al, 2011).…”
Section: Astm C672: Standard Test Methods For Scaling Resistance Of Concrete Surfaces Exposed To De-icing Chemicals (Astm 2012b)mentioning
confidence: 99%
“…In terms of solution and flushing the BNQ follows the procedure of the MTO LS-412 in that a 3% NaCl salt solution is used as the ponding as agent during freeze-thaw cycling and for the flushing process. Bouzoubaâ et al (2011) note that the ASTM C672 does provide for the use of other salt solutions. Finally, the BNQ procedure does differ slightly in the schedule for the removal of the scaled particles.…”
Section: Astm C672: Standard Test Methods For Scaling Resistance Of Concrete Surfaces Exposed To De-icing Chemicals (Astm 2012b)mentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of supplementary cementing materials on salt scaling has been tested by a number of researchers. It was found that the use of fly ash or slag would greatly increase the damage caused by salt scaling (Bouzoubaa et al, 2008(Bouzoubaa et al, , 2011Boyd and Hooton, 2007;Nili and Zaheri, 2011;Ahani and Nokken, 2012;Gagné et al, 2011;Duos and Eggers, 1999;Afrani and Rogers, 1994;Chidiac and Panesar, 2008). The range of replacement varied from 15% up to 50%, with higher levels replacements generally suffering more damage.…”
Section: Effect Of Supplementary Cementing Materialsmentioning
confidence: 99%